Natural Resources, Physical Capital and Institutions : Evidence from Eurasia - Vandycke, Nancy (World Bank, Washington, DC, 2013)
Natural resource abundance can lead to strong economic growth if resource rents are well invested in physical assets and other forms of productive capital. This paper focuses on the case of the resource-abundant economies in Eurasia, which has been less documented in the literature on natural resource-led development than other parts of the world. The analysis shows that the stock of productive physical assets is relatively low, contrary to common perceptions about the Soviet system. The infrastructure that was inherited from the Soviet system primarily serves to meet basic human needs; few assets support the development of competitive and sustainable economies. At a deeper level, the paper documents that low accumulation of physical capital over the past two decades has been driven by weak institutions and economic policies associated with the presence of resource rents, along with a poor public investment management process. This paper complements existing empirical studies by presenting evidence on the mechanisms through which natural resources and physical capital have interacted in setting Eurasian economies on a fragile development path.